2020
DOI: 10.1128/jcm.01973-19
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA and Predictive Model To Improve Diagnosis of Clinically Diagnosed Pulmonary Tuberculosis

Abstract: Clinically diagnosed pulmonary tuberculosis (PTB) patients lack microbiological evidence of Mycobacterium tuberculosis, and misdiagnosis or delayed diagnosis often occurs as a consequence. We investigated the potential of long noncoding RNAs (lncRNAs) and corresponding predictive models to diagnose these patients. We enrolled 1,764 subjects, including clinically diagnosed PTB patients, microbiologically confirmed PTB cases, non-TB disease controls, and healthy controls, in three cohorts (screening, selection, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Therefore, more interests should be given to MPV in the diagnosis of TB. As nomogram for individualized prediction of incident tuberculosis and multidrug‐resistant tuberculosis is convenient, 20 , 41 , 42 two nomograms were produced subsequently, with good discrimination (through AUC) and calibration (via Hosmer–Lemeshow and test calibration curve) (Figure 6 ). However, these results were not very encouraging due to the limitation of sample size, and further study should verify the nomograms and confirm its universality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more interests should be given to MPV in the diagnosis of TB. As nomogram for individualized prediction of incident tuberculosis and multidrug‐resistant tuberculosis is convenient, 20 , 41 , 42 two nomograms were produced subsequently, with good discrimination (through AUC) and calibration (via Hosmer–Lemeshow and test calibration curve) (Figure 6 ). However, these results were not very encouraging due to the limitation of sample size, and further study should verify the nomograms and confirm its universality.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 But the absence of validation limits the applicability of the sequencing findings. Moreover, recent evidence suggested that integrating miRNAs and EHRs could improve the diagnosis for TB patients, 19 , 20 but there are a few reports on this yet.…”
Section: Introductionmentioning
confidence: 99%
“…Each sample was run in triplicate, and the average Cq was calculated. The relative expression of each lncRNA was calculated using the 2-ΔΔCq method and normalized against internal controls ( Hu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, A study validated the lncRNAs and corresponding predictive models to effectively diagnose these patients, finding differentially expressed lncRNAs (ENST00000497872, n333737, n335265) between PTB patients and the healthy group. These lncRNAs might be used as putative biomarkers to facilitate the early identification of PTB cases among suspected patients with negative microbiological evidence ( Table 2 ; Hu et al, 2020 ). In addition, lncRNAs (ENST00000429730.1 and MSTRG.93125.4) were upregulated in lung tissues with high metabolic activity demonstrated by fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography from sputum-negative TB patients compared with low metabolic activity.…”
Section: Long Non-coding Rnas As Diagnosis Biomarkers In Tuberculosismentioning
confidence: 99%